Maize productivity and soil nutrients variations by the application of vermicompost and biochar - Dawar, Khadim; Khan, Ahtesham; Mian, Ishaq Ahmad; Khan, Bushra; Ali, Shamsher; Ahmad, Sagheer; Szulc, Piotr; Fahad, Shah; Datta, Rahul; Hatamleh, Ashraf Atef; Al-Dosary, Munirah Abdullah; Danish, Subhan (PloS one, 2022)
Poor soil organic matter is one of the major causes of the deterioration of soil health. Most soils fertility is also decreased when enough organic carbon is not present in the soil. Maize is most susceptible to this poor soil fertility status. A significant amount of maize growth and yield is lost when it is cultivated in low organic matter and poor fertility soil. To overcome this issue organic amendments can play an imperative role. Biochar and vermicompost are organic amendments that can not only improve organic residues but also increase soil nutrient concentration. The current experiment was conducted to explore the sole and combined application of both organic amendments with recommended NPK fertilizer. Four treatments were tested i.e., control, biochar (BC1), vermicompost (VC1) and VC1+BC1 with and without nitrogen (N), phosphorus (P) and potassium (K) in the experiment. Results showed that VC1+BC1+NPK performed significantly best for improvement in maize plant height (6.25 and 3.00%), 1000 grains weight (30.48 and 29.40%), biological yield (18.86 and 43.12%) and grains yield (30.58 and 39.59%) compared to BC0+VC0+NPK and control respectively. A significant improvement in soil N, P and K also validated the efficacious role of VC1+BC1+NPK over BC0+VC0+NPK and control. Treatment VC1+BC1+NPK is recommended for the achievement of better maize growth and yield in poor organic matter soils. More investigations are suggested in variable climatic conditions to declare VC1+BC1+NPK as the best amendment compared to control for enhancing soil N, P and K status as well as maize productivity.
Keywords: kukuřice setá; zemědělství; Agriculture; Zea mays; průmyslová hnojiva; živiny; půda; Nutrients; Charcoal; Fertilizers; dřevěné a živočišné uhlí; Soil